If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(7b + 15) = 9 + -18b Reorder the terms: -3(15 + 7b) = 9 + -18b (15 * -3 + 7b * -3) = 9 + -18b (-45 + -21b) = 9 + -18b Solving -45 + -21b = 9 + -18b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '18b' to each side of the equation. -45 + -21b + 18b = 9 + -18b + 18b Combine like terms: -21b + 18b = -3b -45 + -3b = 9 + -18b + 18b Combine like terms: -18b + 18b = 0 -45 + -3b = 9 + 0 -45 + -3b = 9 Add '45' to each side of the equation. -45 + 45 + -3b = 9 + 45 Combine like terms: -45 + 45 = 0 0 + -3b = 9 + 45 -3b = 9 + 45 Combine like terms: 9 + 45 = 54 -3b = 54 Divide each side by '-3'. b = -18 Simplifying b = -18
| (5-7i)(3-8i)=0 | | 11-15x-7-6x=7 | | 6+26=-4(2x-8) | | -72+5x=-6x+27 | | -19.4m=-7m-4(3m+17.83) | | 11+1=-4(9x-3) | | 13+2(5c*2)=29 | | -2x-13=-5+5 | | 0=.25x+40 | | -16+12w=7+5+10w | | -6x-13=17-x | | 4(2x+7)=-23+43 | | 4x-(5-x)=35 | | 7(2n+3)=7(7n+5)+5 | | 3b-6+1=2-5b | | 9.4u+19.33-14.71=10.4u+7.82 | | 4x-(5-x)=40 | | 9y+2x^2=0 | | -5(8x+5)=-105 | | 20xcubed-4xsquared-72x= | | -4(6n-5)+3a= | | -2x+X=20-1 | | 5x-11=17+3x | | -2x-7+6(x+1)=-3x-6 | | X-2+x-3=57 | | 15.2d+7.24=-2.6-2.3d+11.59 | | 5(x-4)+6x=3(1-x) | | -9-3x=-5x+9 | | 1w-4=9-1w | | X+x=22+6 | | 28p=6p^2 | | .65X=9.10 |